1972
DOI: 10.1002/pssb.2220500119
|View full text |Cite
|
Sign up to set email alerts
|

Impurity induced Raman spectra of NaCl and KCl crystals with various monovalent impurities

Abstract: Impurity induced Raman spectra have been measured in NaCl:Br, NaCl :I, KCl:I, NaCl:Li, and KCI:Ag. The strongest scattering intensities are caused by A1 vibrations in NaCl:Br, NaCl:I, KC1:I and by E, vibrations in NaCl:Li, KC1:Ag. No Fzg scattering could be found in NaCl:Li and no A1, scattering was observed in KC1:Ag. The position and in part the shape of the scattering spectra are discussed. The measured scattering intensities are compared firstly with the polarizabilities (for impurities and neighbours) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1972
1972
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…If one assumes, for example, that the defect has a dominating breathing degree of freedom, then the correspondingly strong contribution from to the spectrum of the scattered light has breathing (1;+, A 1g ) symmetry. This picture seems to be supported by Raman measurements by MOLLER and KAI-SER (1972, KAISER andMOLLER, 1969). They find groups of systems.…”
Section: Wlmu=gu-gs 0= -Gu+(2f+g)ssupporting
confidence: 48%
See 1 more Smart Citation
“…If one assumes, for example, that the defect has a dominating breathing degree of freedom, then the correspondingly strong contribution from to the spectrum of the scattered light has breathing (1;+, A 1g ) symmetry. This picture seems to be supported by Raman measurements by MOLLER and KAI-SER (1972, KAISER andMOLLER, 1969). They find groups of systems.…”
Section: Wlmu=gu-gs 0= -Gu+(2f+g)ssupporting
confidence: 48%
“…They do have minor differences in the dispersion curves which show up as different peak positions, but the corresponding eigenvectors seem very similar as is indicated by the approximately equal peak intensities, although these are an integral of the amplitudes over a certain frequency range. Ag+ impurities and later a series of defects in NaCI and KCI crystals have been investigated by KAISER and MOLLER (1969);MOLLER and KAISER (1972); KAISER et al (1973);MONTGOMERY et al (1972a);and HONER ZU SIEDERDISSEN (1976); a pair vibration has been found also (MOLLER et aI., 1970). Cu + impurities have been studied by MONTGOMERY and KIRBY (1971);GANGULY et al (1972); and in a special context by IVANOV and PINKEVICH (1975).…”
Section: N Dn=2s ; L E"(pjep(ps)f!i<>x"pi<>x'p)e(pjep'(ps)·mentioning
confidence: 94%
“…The re-16. sults for Ag+, Br-, and Icentres are taken from Moller and Kaiser [9]. The table is divided into three groups:…”
Section: Pb++ Srf+ and Ca++ Centresmentioning
confidence: 99%
“…The first-order spectrum of KCl(Itb+) is less than one fifth of the KCl(Sr++) spectrum although the concentrations are in the same order of magnitude. The Raman spectra of KCl(Ag+) and KCl(I-) have been published by Moller and Kaiser [9]. The impurity concentration is indicated as 2.5 x 1020 cm-3.…”
Section: Pb++ Srf+ and Ca++ Centresmentioning
confidence: 99%
“…[6][7][8] The impurity-induced vibration modes of KI:Ag þ were extensively studied by Sievers and coworkers using Raman and IR spectroscopies. [9][10][11][12][13] In the present study, we examine the impurity vibrational states by first principles calculations. Results are compared with the experimental data in order to examine the accuracy and limitations of such calculations.…”
Section: Introductionmentioning
confidence: 99%